Effect of water vapour on the oxidation of Fe-Cr-Ni alloy at 1073 K - Akhbar bin Kaderi (Kulliyyah of Engineering, International Islamic University Malaysia, 2013)
Ferritic Fe-9 to 12%Cr alloy has its importance in the development of the new generation Ultra-Supercritical (USC) Power Plant because the targeted operating temperature is reaching 973 K, in 100% steam condition and pressure in excess of 30 × 106 Pa. In such condition, the integrity of Fe-9 to 12%Cr alloy relies on the oxide scale formed during the time of exposure. Various studies showed that the protective oxide scale degraded in the presence of water vapour. Understanding on this mechanism has yet to reach any conclusion. These led to the need of studying the initial stage oxidation of these alloys in water vapour condition at high temperature. This work is giving special attention to the effect of water vapour on the formation of voids in the oxide scale and the changes in the surface energy prior to oxidation. These voids will affect the mechanical property of scales through cracking and spalling. Fe-Cr-Ni alloy with thickness of 1 mm and Cr samples with dimensions 10 mm × 10 mm × 1 mm were exposed isothermally at 1073 K in air (PO2 )= 2.1×105 Pa) and humid (air + steam) environments. XRD analysis confirms that Fe2O3, Fe3O4, NiCr2O4, FeCr2O4, Cr2O3 and NiO exist in the scale of Fe-Cr-Ni alloy. EDX analysis shows compositions of Fe, Cr, Ni and O varied in outer and inner oxide scale, oxide scale/metal interface and metal. Volume fraction of voids in the oxide scale calculated based on the FE-SEM's micrograph of the cross sectional area fraction of voids in the scale. Fe-Cr-Ni alloy samples exposed in humid environment has as high as 86% more voids than that exposed in dry environment. The humid environment increased the number of void formed in the oxide scale, thus facilitates the exfoliation of protective scale during the high temperature oxidation. The effects of water vapour on the surface energy of metal were performed on Cr metals. XRD analysis on all samples shows that Cr2O3 can be formed in dry and humid environment. SEM reveals the surface oxide morphology consisting of nodule-like structure in dry samples and whisker-like structure in humid samples. IR transmission spectra for samples oxidized in dry environment, were consisting of more intense peak while samples oxidized in humid environment has more relaxed peak. Based on these evidences, adsorption of water occurred during the oxidation contributed to the increases in oxidation rate of Cr. This could be explained by the increased catalytic activity on the surface of the metal. The increased in catalytic activity correlated with the increase in surface energy as proven by the study on the Cr metal. The increased in surface energy facilitates the solubility and diffusivity of oxidant and cation into the metal or alloy. This has caused greater volume of void formed in humid environment as demonstrated in the oxidation of Fe-Cr-Ni alloy. It is concluded that void formation and surface energy changes played greater role in increasing the oxidation rate of ferritic alloy in humid environment.